An Examination of Wage and Income Inequality within the American Farmworker Community. (September 2018) - Bowers, Marianne L.; Chand, Daniel E.
This article explores the reasons for earning inequalities among farmworkers. Using national data from the US Department of Labor's National Agricultural Worker Survey (NAWS), we detail and examine differences in earnings among farmworkers based on certain characteristics identified in prior literature. We find that gender and youth are the most reliable predictors of farmworker earnings, with females and workers under 21 consistently earning less than other categories of farmworkers. In addition, we find that workers who seasonally follow crops are among the lowest earning farmworkers. We also confirm that, as expected, workers lacking authorized status earn less than those who have legal status. Surprisingly, however, foreign-born US citizens actually earn more than their US-born counterparts. These findings have substantial implications for policymakers and labor advocates who seek to improve the plight of US farmworkers.